Trends in African Americans' Attitudes and Behaviors About Living Donor Kidney Transplantation. (December 2018) - Vilme, Helene; Davenport, Clemontina A.; Pendergast, Jane; Boulware, L. Ebony
Background: Due to marginal efforts to increase living donor kidney transplantation, it is unclear whether interventions to improve African Americans' interest and pursuit of living donation should be tailored to address patients' exposure to or familiarity with dialysis or transplant settings. Design, Setting, and Participants: We conducted a cross-sectional secondary analysis of baseline data from 3 separate randomized clinical trials among African Americans with varying degrees of experience with dialysis or transplantation (predialysis, on dialysis but not on transplant list, and on transplant wait-list) settings. Methods: Interest in living donation was described using a 0 to 10 scale and pursuit of living donor kidney transplantation by achievement of at least 1 pursuant behavior. In multivariable logistic regression analyses, we assessed the association of knowledge, health literacy, and trust in health care with interest in or pursuit of living donation. Results: Interest among the 3 study cohorts was high (predialysis, 62.9%; dialysis, 67.4%; and transplant wait-list, 74.2%). The dialysis and transplant wait-list study cohorts pursued living donation more readily than those not on dialysis (73%, 92%, and 45%, respectively). Interest and pursuit were not statistically significantly associated with knowledge, health literacy, or the 3 factors reflecting medical mistrust. Conclusion: Interest and pursuit of living donation were greater among study participants with greater exposure to dialysis or transplant settings. Efforts to promote patients' early interest and pursuit of living donor transplants may consider novel strategies to educate patients with less experience about the benefits of living donor kidney transplantation.